Evaluation of sesame (Sesamum indicum L.) varieties for drought tolerance using agromorphological traits and drought tolerance indices - Getahun Yemata; Tewachew Bekele (PeerJ, 2024)
Sesame (Sesamum indicum L.) is an important cash crop cultivated under rain-fed conditions where it contributes a significant proportion of Ethiopia’s foreign exchange earnings. However, its productivity is constrained by drought stress. The present study aimed to evaluate the agromorphological and yield performance of sesame varieties and to identify drought tolerant varieties using drought tolerance indices. The sesame varieties were evaluated under well-watered (WW) and water-stressed (WS) field conditions with a factorial design laid down in randomized complete block design in three replications. The results revealed the presence of a significant variation in agromorphological traits and drought tolerance indices due to water levels, varieties and their interactive effect. On average, a 21.8, 49.6, 48.4, 47.9 and 21.7% reduction was recorded in plant height, number of leaves per plant, leaf length, leaf width and relative growth rate (RGR), respectively under WS condition. Similarly, a significant reduction was found in shoot biomass, root biomass, biological yield, number of pods per plant and seed yield under WS condition. These traits showed an average reduction of 52.2, 72.5, 54.0, 51.9 and 52.8%, respectively compared to WW condition. The highest yield reduction was recorded from wollega under WS condition, while the lowest was from abasena. Wollega variety produced the highest seed yield (kg/ha) under WW condition, while gondar-1 and humera-1 had the highest yield in kg/ha under WS condition. Under both water levels, abasena produced the lowest yield (kg/ha). Moreover, gondar-1 and humera-1 varieties had a comparatively higher values of stress tolerance index (STI), yield stress score index (YSSI), yield potential score index (YPSI), geometric mean productivity (GMP) and mean productivity (MP) that are significantly and positively correlated with yield under WS, indicating higher yield performance under water stress. The biplot analysis clustered the varieties as low yielding (abasena) and relatively above average performing varieties (humera-1, gondar-1 and wollega). According to the rank sum of all indices, humera-1 was identified as drought tolerant, while abasena as the most susceptible and low yielding varieties. Thus, humera-1 followed by gondar-1 were found to be drought tolerant and high yielding varieties. However, further studies focusing on drought tolerance mechanisms of the varieties are recommended.